AI Enhanced BI for Dynamic Portfolio Optimization under Market Volatility - Rajesh Aakula (International Journal of Intelligent Systems and Applications in Engineering, 2025)
Volatile markets make it hard to invest because the values keep fluctuating and there is uncertainty in the market. This is because strategic investment principles may not be suitable to make high-speed movements that may bring low returns or increase risk. BI integrated with Artificial Intelligence (AI) has the benefit of real-time analysis and dynamically designed decision tools that provide constant portfolio fine-tuning. This is an ability offered by AI that involves analyzing high levels of data, detecting market trends, and controlling assets to keep the portfolio on course towards its goal amidst fluctuation. This integration makes dynamic rebalancing possible such that the portfolio is realigned back to real market terms to reduce risk and maximize return. With these technologies, portfolio managers have an easy time coping with risks in the market and offering better investment propositions that are dynamic and technology reliant. Combining artificial Intelligence and Business Intelligence is an efficient way to maximize portfolio management in the modern and uncertain financial environment.